Genome wide array comparative genomic hybridisation analysis of premalignant lesions of the stomach. Issue 5 (26th September 2003) - Weiss, M M; Kuipers, E J; Postma, C; Snijders, A M; Stolte, M; Vieth, M; Pinkel, D; Meuwissen, S G M; Albertson, D; Meijer, G A
Abstract : Background: Gastric cancer is one of the most frequent malignancies in the world, ranking fifth in the Netherlands as a cause of cancer death. Surgery is the only curative treatment for advanced cases, but results of gastrectomy largely depend on the stage of the disease. A better understanding of the mechanisms of progression from a preneoplastic condition through intraepithelial neoplasia to invasive cancer may provide information relevant to designing focused prevention strategies. Methods: Because the pattern of chromosomal aberrations in precursors of gastric cancer is unclear, 11 gastric polyps with intraepithelial neoplasia (three hyperplastic polyps and eight adenomas) were analysed by microarray comparative genomic hybridisation to study chromosomal instability in precursors of gastric cancer. Results: Chromosomal aberrations were detected in all specimens. Adenomas showed no more chromosomal aberrations than did the hyperplastic polyps. The most frequent aberrations were gain of 7q36 and 20q12, and loss of 5q14–q21 in the adenomas, and loss of 15q11–14, 1p21–31, and 21q11–21.2 in the hyperplastic polyps. The most frequent chromosomal aberration in common to both types was loss of 9p21.3. Conclusion: Hyperplastic polyps showed many chromosomal aberrations, confirming that neoplastic transformation can occur in these lesions. These observations are consistent with the existence of two morphologically and genetically distinct pathways to gastric cancer—the hyperplastic polyp pathway and the (intestinal type) adenoma pathway. The relative contribution of each to gastric carcinogenesis in general, and how they compare to patterns of chromosomal aberrations in the more prevalent flat foci of intraepithelial neoplasia remain to be determined.